Road Warriors: Fostering Object-Learner Assemblages Through a Social Context of Embodied Learning - Jonathan A. Crothers MS (Adult Education Research Conference, 2018)
This study investigates how adults informally learn through engaging with the object of their bicycles in the social context of the sport of amateur road racing, and explores how this learning has shaped their individual and social identities.
Keywords: Embodied Learning; Actor Network Theory; Leisure Sports